Thea Stilton and the Secret of the Old Castle - Stilton, Thea (Scholastic Inc., 2009)
Geronimo's sister Thea Stilton narrates this action-packed adventure! When the Thea Sisters' friend Bridget returns to Scotland for a family emergency, the five mice offer to help. And when Bridget goes missing, they have to rush to Scotland to help find her! Along the way, the Thea Sisters encounter Celtic legends, cryptic messages, and hidden treasures on a trip that's full of surprises!